Overexpression of AtGRDP2, a novel glycine-rich domain protein, accelerates plant growth and improves stress tolerance - Ortega-Amaro, María A.; Rodríguez-Hernández, Aída A.; Rodríguez-Kessler, Margarita; Hernández-Lucero, Eloísa; Rosales-Mendoza, Sergio; Ibáñez-Salazar, Alejandro; Delgado-Sánchez, Pablo; Jiménez-Bremont, Juan F. (Frontiers in Plant Science, 2015)
Proteins with glycine-rich signatures have been reported in a wide variety of organisms including plants, mammalians, fungi, and bacteria. Plant glycine-rich protein genes exhibit developmental and tissue-specific expression patterns. Herein, we present the characterization of the AtGRDP2 gene using Arabidopsis null and knockdown mutants and, Arabidopsis and lettuce over-expression lines. AtGRDP2 encodes a short glycine-rich domain protein, containing a DUF1399 domain and a putative RNA recognition motif. AtGRDP2 transcript is mainly expressed in Arabidopsis floral organs, and its deregulation in Arabidopsis Atgrdp2 mutants and 35S::AtGRDP2 over-expression lines produces alterations in development. The 35S::AtGRDP2 over-expression lines grow faster than the WT, while the Atgrdp2 mutants have a delay in growth and development. The over-expression lines accumulate higher levels of indole-3-acetic acid and, have alterations in the expression pattern of ARF6, ARF8 and miR167 regulators of floral development and auxin signaling. Under salt stress conditions, 35S::AtGRDP2 over-expression lines displayed higher tolerance and increased expression of stress marker genes. Likewise, transgenic lettuce plants over-expressing the AtGRDP2 gene manifest increased growth rate and early flowering time. Our data reveal an important role for AtGRDP2 in Arabidopsis development and stress response, and suggest a connection between AtGRDP2 and auxin signaling.